BIRDEM News - Microbiology: Bacteria and Antibiogram Report (July to December 2012 Report) - Editor, The (BIRDEM Medical Journal, 2013)
Birdem Med J 2013; 3(2): 126-129 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17223